2020
DOI: 10.25248/reas.e4006.2020
|View full text |Cite
|
Sign up to set email alerts
|

Impactos no comportamento e na saúde mental de grupos vulneráveis em época de enfrentamento da infecção COVID-19: revisão narrativa

Abstract: Objetivo: Realizar uma revisão narrativa das repercussões no comportamento e na saúde mental da população vulnerável e de medidas adotadas, no enfrentamento da pandemia do COVID-19. Revisão bibliográfica: Devido imprevisibilidade da pandemia do COVID-19, consequências mentais, são cada vez mais relatadas. Suspeitos, infectados, profissionais de serviços essenciais, os que vivem sozinhos, instituições como casas de repouso, prisões, centros de detenção de imigrantes, idosos, portadores de doença mental, imunode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
51

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 4 publications
0
10
0
51
Order By: Relevance
“…The comparison between the various dimensions that acted as predictors of depressive symptoms showed that age, gender, and sexual orientation, but mostly fear and the negative impact of COVID-19 contributed to the explanation of the depressive symptoms. The fact that the pandemic has had an impact on the health system, politics, the economy and education can be reflected in the appearance of several mental disorders, namely depression [ 16 ]. Women and individuals belonging to sexual minorities may have seen greater negative impact from COVID-19 and had higher levels of depression [ 52 ] and this level of concern and fear can be highly disabling [ 6 , 8 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison between the various dimensions that acted as predictors of depressive symptoms showed that age, gender, and sexual orientation, but mostly fear and the negative impact of COVID-19 contributed to the explanation of the depressive symptoms. The fact that the pandemic has had an impact on the health system, politics, the economy and education can be reflected in the appearance of several mental disorders, namely depression [ 16 ]. Women and individuals belonging to sexual minorities may have seen greater negative impact from COVID-19 and had higher levels of depression [ 52 ] and this level of concern and fear can be highly disabling [ 6 , 8 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the psychological implications related to COVID-19, measures implemented to contain the disease may also consist of risk factors for mental health [ 6 ]. Social distancing and other measures that suspend day-to-day activities, despite protecting the physical health of the population, are associated with the development of various disorders, such as depression [ 4 , 14 , 15 , 16 ]. In this sense, negative effects were identified, such as symptoms of post-traumatic stress, confusion and anger at the measures implemented [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though it is essential for the containment of the pandemic, social distancing brought relevant psychic disorders related to the feeling of loneliness and isolation from family and friends, changes in socioeconomic context, lack of control over one's own life and fear of getting sick 30,31 . In Brazil, we observed large proportions of individuals who often felt isolated, sad or depressed, anxious or nervous, as well as people who reported having trouble sleeping.…”
Section: Discussionmentioning
confidence: 99%
“…Em contraposição a isso, observa-se a profusão da produção científica destacando os efeitos da pandemia na saúde mental de diferentes grupos e em contextos sociais, dentre os quais situam-se migrantes, população em privação de liberdade, portadores de doenças crônicas e pessoas com histórico de sofrimento psíquico (Pires, 2020;Lima et al, 2020;Garrido & Rodrigues, 2020). Essa produção representa uma iniciativa de romper com o "silenciamento da cultura" na política e nos serviços de saúde mental, indicado por Ortega e Wenceslau (2019, p. 58), no que se refere à ausência das causas sociais e econômicas, das variadas concepções e crenças associadas à saúde mental e às formas de tratamento e cura produzidas em um país multicultural como o Brasil.…”
Section: Saúde Mental Iniquidades Sociais E Fascismo Viralunclassified